Enterococcal peritonitis in children receiving chronic peritoneal dialysis - Sutherland, Scott M.; Alexander, Steven R.; Feneberg, Reinhard; Schaefer, Franz; Warady, Bradley A. (Nephrology, dialysis, transplantation, 2010)
Background. Peritonitis is a common complication of chronic peritoneal dialysis (CPD) and can be associated with technique failure. Enterococcus is an uncommon peritoneal pathogen in children receiving CPD but represents a potential therapeutic challenge due to its innate resistance to cephalosporins and emerging resistance to glycopeptides.Methods. The International Pediatric Peritonitis Registry is a global consortium of 47 paediatric dialysis centres designed to address validation of the International Society for Peritoneal Dialysis paediatric peritonitis treatment guidelines. Between 2001 and 2004, peritonitis episodes were assessed in 392 participating children receiving CPD.Results. Among the 392 patients, 340 episodes of culture-positive peritonitis were evaluated. Twenty of these episodes were due to Enterococcus species (5.9%). There were no clinical characteristics uniquely associated with enterococcal peritonitis at presentation. After 3 days of therapy, 75% of patients were pain free, 95% had decreased effluent cloudiness and 90% were afebrile. Only one patient required a catheter exchange, and all patients experienced full functional recovery. Despite broad in vitro resistance to cephalosporins and 21% resistance to glycopeptides, neither in vitro resistance pattern nor choice of empiric antibiotic regimen affected short- or long-term outcomes.Conclusions. Enterococci are likely responsible for ∼6% of culture-positive peritonitis episodes in children receiving CPD. Although it was not possible to identify patients with enterococcal peritonitis based on presentation, clinical response was not associated with in vitro resistance patterns, and patients who initially received a cephalosporin-based empiric regimen until culture results are available are likely to respond quickly and have full functional recovery.